PARENTAL ATTENTION, LEARNING MOTIVATION, EMOTIONAL INTELLIGENCE AND INFLUENCE ON LEARNING OUTCOMES - Hikmah, Umi Nurul; Mardi; Prihatni, Rida (Transpublika Publisher, 2022)
The purpose of this study is to determine the effect of parental attention, learning motivation, and emotional intelligence on student learning outcomes in basic accounting subjects for class X at SMK Negeri in East Jakarta. This study's population consisted of students enrolled in class X Accounting at State Vocational Schools in East Jakarta, with an accessible population of 213 students and a sample size of 138 respondents. The t-test and F tests are used to test the hypothesis in this study. The t-test results indicate that there is a positive and marginally significant relationship between parental attention and learning outcomes, learning motivation and learning outcomes, and emotional intelligence and learning outcomes. The results of the F test indicate that parental attention, learning motivation, and emotional intelligence have a positive and statistically significant effect on academic achievement. The influence of parental attention, learning motivation, and emotional intelligence on learning outcomes yielded a coefficient of determination of 13.4%; the remaining variance was attributable to unmeasured factors.